Arabic Conversation Learning Activities with the Real Player Application - Abdullah, Ahmad Hafidz; Maturedy, Faris (Journal of Arabic Language Studies and Teaching, 2023)
This study aims to describe the activity of teaching conversation in Arabic for the second grade of MTs Miftahul Ulum, including the teacher's use of the RealPlayer application. This study used the qualitative research methodology as a case study. The data were therefore collected in two ways: participatory observation and personal interview. An Observation to know the steps of dialogue teaching activities and students' responses throughout the education process. As for the personal interview, it is to confirm and reconcile the data taken from the observation. The participants are the students in the second semester and the Arabic language teacher. After the data was collected, it was analyzed using the Miles and Huberman model, which consists of three steps: the presentation and reduction of data and the conclusion. Eventually, the researchers came to conclusions. The first is that the teacher begins teaching conversation in the second semester by reviewing the material in a continuous training manner. The teacher thus continued to teach conversation with the main activities with the help of means, including the RealPlayer app and the speaker. The confirmation activities were conducted through discussion between the students and the teacher using the RealPlayer application.